2014
DOI: 10.1016/j.neuron.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Configural and Elemental Coding of Natural Odor Mixture Components in the Human Brain

Abstract: SUMMARY Most real-world odors are complex mixtures of distinct molecular components. Olfactory systems can adopt different strategies to contend with this stimulus complexity. In elemental processing, odor perception is derived from the sum of its parts; in configural processing, the parts are integrated into unique perceptual wholes. Here we used gas-chromatography/mass-spectrometry techniques to deconstruct a complex natural food smell and assess whether olfactory salience is confined to the whole odor or is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 69 publications
(102 reference statements)
7
59
0
1
Order By: Relevance
“…Multivariate fMRI pattern analyses have shown that distributed ensemble representations in the PC exhibit greater pattern overlap for odor stimuli belonging to the same perceptual category [50]. A recent study demonstrated that the posterior PC encodes value-based ensemble codes of a complex natural food-odor (peanut butter), but not its chemical components [51], consistent with the idea of configural processing in this area. Non-olfactory cues may also elicit odorspecific distributed patterns in the posterior PC in advance of odor input [52,53], suggesting that this area receives top-down projections to facilitate olfactory predictive coding and rapid processing [29].…”
Section: A Neuro-cognitive Framework For Odor Namingmentioning
confidence: 77%
“…Multivariate fMRI pattern analyses have shown that distributed ensemble representations in the PC exhibit greater pattern overlap for odor stimuli belonging to the same perceptual category [50]. A recent study demonstrated that the posterior PC encodes value-based ensemble codes of a complex natural food-odor (peanut butter), but not its chemical components [51], consistent with the idea of configural processing in this area. Non-olfactory cues may also elicit odorspecific distributed patterns in the posterior PC in advance of odor input [52,53], suggesting that this area receives top-down projections to facilitate olfactory predictive coding and rapid processing [29].…”
Section: A Neuro-cognitive Framework For Odor Namingmentioning
confidence: 77%
“…For example, one study 17 implicated that subjective preference for food items can be expressed as a linear combination of various nutritive attributes, such as an item's sugar and fat content. Another study suggested a similar coding of odor mixture components in food, 18 where the values of individual order components, as well as the value of food as a whole, were tracked by orbitofrontal cortex (OFC). Further evidence supports attribute-based computations in prefrontal cortex (PFC), such as the distinction between whether a food is judged to be tasty or healthy, 19 or even in judgments about the value of clothing, 20 as well as the value of multi-attribute artificial stimuli (e.g., the movement and the color of dots) in humans and macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Since naturalistic odor stimuli are complex blends of many odorants, even relatively simple odor blends may saturate the entire complement of OSNs, thereby limiting their information coding capacity. More generally, even before saturation sets in, nonlinear interactions among multiple odorants in a given OSN may pose challenges for downstream decoding of odor identity (Howard and Gottfried, 2014;Wilson and Sullivan, 2011).…”
Section: Introductionmentioning
confidence: 99%